PEMBELAJARAN IPS DENGAN MODEL CTL MATERI PERDAGANGAN INTERNASIONAL PADA SISWA IX G SMPN 11 KOTA CIREBON - Leni Herliani; Eulis Henda Nugraha (Jurnal Investasi, 2020)
This study raises a learning phenomenon in the classroom which is packaged in a Classroom Action Research with the title "Social Studies Learning with the CTL Model of International Trade Materials for Class IX G Students of SMPN 11 Cirebon". This study uses qualitative methods and observation techniques with an emphasis on the learning process in the classroom. The population in this study was 37 students, consisting of 19 male students and 18 female students. The research sample is class IX G students in the odd semester of SMP Negeri 11 Cirebon for the 2019-2020 academic year. The data collected comes from CAR which includes: 1) Planning, 2) Implementation, 3) Observation, and 4) Reflection in two cycles. The findings of this study are as follows: (1) generally students' attention to the learning process increases, (2) students' courage increases, (3) the quality of students' answers increases, (4) the seriousness and ability of students to ask questions increases, (5) ability and foresight students to avoid mistakes in answering the teacher's questions increase, (6) attention, ways, seriousness and ability of students in solving difficult or not difficult questions increase, (7) students who ask questions, responses, comments, suggestions, and criticisms of the questions given teachers increase, (8) the number of students who get an increase in grades from the previous increase, (9) the number of students who get a decrease in grades from before is reduced, (10) student learning outcomes both individually and in groups have increased, in the first cycle of the average an average of 5.65 to 8.20 in the second cycle, an increase of 45.13%. Information from students' feedback also showed that CTL learning received a positive response as evidenced by an average of 2.72 (good). This shows that students are happy with using CTL learning.  Based on the findings above, the researcher recommends that learning with the CTL learning model in general can be used as a model in money learning.